Decay-accelerating factor must bind both components of the complement alternative pathway C3 convertase to mediate efficient decay. - Harris, C; Pettigrew, D; Lea, S; Morgan, B (2007)
Decay-accelerating factor (DAF; CD55) inhibits the complement (C) cascade by dissociating the multimolecular C3 convertase enzymes central to amplification. We have previously demonstrated using surface plasmon resonance (Biacore International) that DAF mediates decay of the alternative pathway C3 convertase, C3bBb, but not of the inactive proenzyme, C3bB, and have shown that the major site of interaction is with the larger cleavage subunit factor B (Bb) subunit. In this study, we dissect these interactions and demonstrate that the second short consensus repeat (SCR) domain of DAF (SCR2) interacts only with Bb, whereas SCR4 interacts with C3b. Despite earlier studies that found SCR3 to be critical to DAF activity, we find that SCR3 does not directly interact with either subunit. Furthermore, we demonstrate that properdin, a positive regulator of the alternative pathway, does not directly interact with DAF. Extending from studies of binding to decay-accelerating activity, we show that truncated forms of DAF consisting of SCRs 2 and 3 bind the convertase stably via SCR2-Bb interactions but have little functional activity. In contrast, an SCR34 construct mediates decay acceleration, presumably due to SCR4-C3b interactions demonstrated above, because SCR3 alone has no binding or functional effect. We propose that DAF interacts with C3bBb through major sites in SCR2 and SCR4. Binding to Bb via SCR2 increases avidity of binding, concentrating DAF on the active convertase, whereas more transient interactions through SCR4 with C3b directly mediate decay acceleration. These data provide new insights into the mechanisms involved in C3 convertase decay by DAF.